2019
DOI: 10.4274/tjh.galenos.2018.2018.0325
|View full text |Cite
|
Sign up to set email alerts
|

A Novel ATP6V0A2 Mutation Causing Recessive Cutis Laxa with Unusual Manifestations of Bleeding Diathesis and Defective Wound Healing

Abstract: Objective: Autosomal recessive cutis laxa type IIA (ARCL2A) is a rare congenital disorder characterized by loose and elastic skin, growth and developmental delay, and skeletal anomalies. It is caused by biallelic mutations in ATP6V0A2 . Those mutations lead to increased pH in secretory vesicles and thereby to impaired glycosyltransferase activity and organelle trafficking. We aimed to identify the genetic and molecular cause of the unexpected hematological findings in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Literature review identified 14 articles published from 2005 to 2019 with individuals with ARCL2A or WSS due to deleterious variants in ATP6V0A2 (Medrano et al, 2019: Karacan et al, 2019; Beyens et al, 2019; Kariminejad et al, 2017; Ritelli et al, 2014; Bahena‐Bahena et al, 2014; Gardeitchik et al, 2014; Greally et al, 2014; Fischer et al, 2012; Hucthagowder et al, 2009; Kornak et al, 2008; Mohamed et al, 2011; Morava et al, 2005; Tantcheva‐Poor et al, 2012). A total of 70 affected individuals from 65 families, including ours, were found (Tables S1–S4).…”
Section: Resultsmentioning
confidence: 99%
“…Literature review identified 14 articles published from 2005 to 2019 with individuals with ARCL2A or WSS due to deleterious variants in ATP6V0A2 (Medrano et al, 2019: Karacan et al, 2019; Beyens et al, 2019; Kariminejad et al, 2017; Ritelli et al, 2014; Bahena‐Bahena et al, 2014; Gardeitchik et al, 2014; Greally et al, 2014; Fischer et al, 2012; Hucthagowder et al, 2009; Kornak et al, 2008; Mohamed et al, 2011; Morava et al, 2005; Tantcheva‐Poor et al, 2012). A total of 70 affected individuals from 65 families, including ours, were found (Tables S1–S4).…”
Section: Resultsmentioning
confidence: 99%
“…Qualitative or quantitative deficiency of plasma VWF multimers causes a bleeding disorder called von Willebrand disease ( Sadler, 2005 ; Sadler, 1998 ; Sharma and Haberichter, 2019 ). A V0a2 mutation has recently been reported to cause bleeding diathesis in humans ( Karacan et al, 2019 ). Plasma VWF activity is significantly impaired in patients without any substantial loss of plasma VWF antigen level, thus exhibiting a typical sign of von Willebrand disease, although no associating mutation was found in the VWF gene.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our justification for using a porcine valve prosthesis instead of a mechanical valve in this patient is the social status, as this patient lives in a remote suburb area with difficult access to tertiary care centers making it difficult to comply with anticoagulant therapy. Furthermore, based on the literature, Karacan et al demonstrated CCL syndrome to be a notoriously unexpectable disorder with multiple cases reported to have abrupt bleeding diathesis and defective wound healing [ 16 ]. To the best of our knowledge, this is the first case reported in the literature with successful surgical treatment of both mitral and tricuspid valves associated with this syndrome.…”
Section: Discussionmentioning
confidence: 99%